Improving LCC Series-Based Wireless Power Transfer System Output Power at High Temperature - Chien-Lung Chen (MDPI AG, 2021)
Adding a core to a coupling coil can improve transmission efficiency. However, the added core causes the self-inductance of the coupling coil to increase at a high temperature due to the temperature-sensitive property of the core material’s permeability. The self-inductance increases, causing the resonance frequency to shift down, thereby decreasing the output power. The 3 dB bandwidth of the system can learn of the correspondence between the output power and the resonance frequency. In order to make sure that the output power does not excessively decrease at a high temperature, this study employs a simulation for the LCC-S-based wireless power transfer system. Adding a minor resistance to shift down the lower cutoff frequency ensures that the resonance frequency yielded by the temperature rise can be higher than the lower cutoff frequency, making the output power higher than half of the maximum. Then, an adjustment on the compensation capacitances on the resonant circuit elevates the output power more. The outcomes are consistent with the prediction. Adding the core to the coupling coil improves transmission efficiency; increasing the bandwidth of the system excessively decreases the output power decline at a high temperature for the temperature-sensitive core material permeability.